World Development Report 2013 : Jobs - World Bank (Washington, DC, 2012)
Jobs provide higher earnings and better benefits as countries grow, but they are also a driver of development. Poverty falls as people work their way out of hardship and as jobs empowering women lead to greater investments in children. Efficiency increases as workers get better at what they do, as more productive jobs appear, and less productive ones disappear. Societies flourish as jobs bring together people from different ethnic and social backgrounds and provide alternatives to conflict. Jobs are thus more than a byproduct of economic growth. They are transformational—they are what we earn, what we do, and even who we are. High unemployment and unmet job expectations among youth are the most immediate concerns. But in many developing countries, where farming and self-employment are prevalent and safety nets are modest at best, unemployment rates can be low. In these countries, growth is seldom jobless. Most of the poor work long hours but simply cannot make ends meet. And the violation of basic rights is not uncommon. Therefore, the number of jobs is not all that matters: jobs with high development payoffs are needed. Confronted with these challenges, policy makers ask difficult questions. Should countries build their development strategies around growth, or should they focus on jobs? Can entrepreneurship be fostered, especially among the many microenterprises in developing countries, or are entrepreneurs born? Are greater investments in education and training a prerequisite for employability, or can skills be built through jobs? In times of major crises and structural shifts, should jobs, not just workers, be protected? And is there a risk that policies supporting job creation in one country will come at the expense of jobs in other countries? The World Development Report 2013: Jobs offers answers to these and other difficult questions by looking at jobs as drivers of development—not as derived labor demand—and by considering all types of jobs—not just formal wage employment. The Report provides a framework that cuts across sectors and shows that the best policy responses vary across countries, depending on their levels of development, endowments, demography, and institutions. Policy fundamentals matter in all cases, as they enable a vibrant private sector, the source of most jobs in the world. Labor policies can help as well, even if they are less critical than is often assumed. Development policies, from making smallholder farming viable to fostering functional cities to engaging in global markets, hold the key to success.